The Chemostratigraphy of the Murray Formation and Role of Diagenesis at Vera Rubin Ridge in Gale Crater, Mars, as Observed by the ChemCam Instrument. Issue 9 (12th September 2020) - Frydenvang, J.; Mangold, N.; Wiens, R. C.; Fraeman, A. A.; Edgar, L. A.; Fedo, C. M.; L'Haridon, J.; Bedford, C. C.; Gupta, S.; Grotzinger, J. P.; Bridges, J. C.; Clark, B. C.; et al.
Abstract: Geochemical results are presented from Curiosity's exploration of Vera Rubin ridge (VRR), in addition to the full chemostratigraphy of the predominantly lacustrine mudstone Murray formation up to and including VRR. VRR is a prominent ridge flanking Aeolis Mons (informally Mt. Sharp), the central mound in Gale crater, Mars, and was a key area of interest for the Mars Science Laboratory mission. ChemCam data show that VRR is overall geochemically similar to lower‐lying members of the Murray formation, even though the top of VRR shows a strong hematite spectral signature as observed from orbit. Although overall geochemically similar, VRR is characterized by a prominent decrease in Li abundance and Chemical Index of Alteration across the ridge. This decrease follows the morphology of the ridge rather than elevation and is inferred to reflect a nondepositionally controlled decrease in clay mineral abundance in VRR rocks. Additionally, a notable enrichment in Mn above baseline levels is observed on VRR. While not supporting a single model, the results suggest that VRR rocks were likely affected by multiple episodes of postdepositional groundwater interactions that made them more erosionally resistant than surrounding Murray rocks, thus resulting in the modern‐day ridge after subsequent erosion. Plain Language Summary: Results from the ChemCam instrument on Vera Rubin ridge (VRR) in Gale crater, Mars, are presented and compared with observations from similar rocks leading up to the ridge. VRR is a prominent ridge, flanking the central mound, Aeolis Mons, in Gale crater, Mars. The ridge attracted early attention because it displays strong iron‐oxide spectral signatures. Surprisingly, ChemCam data show that VRR rocks do not show an overall increase in iron abundance relative to the comparable bedrock analyzed for almost 300 m in elevation leading up to the ridge. While similar overall, some notable variations were observed on VRR relative to lower‐lying rocks. In particular, geochemical variations suggest a strong decrease in clay content on the ridge, above which, a notable enrichment in Mn is observed. No single geological process confidently explains all observations on the ridge. Rather, we think that VRR rocks underwent a series of interactions with groundwater that caused the rocks of VRR to become more resistant to erosion than their surroundings, thus emerging as a ridge as the rocks around them eroded. This likely implies that groundwater persisted in Gale crater even long after the disappearance of the ancient lake. Key Points: A decrease in Li and Chemical Index of Alteration, reflecting clay mineral content, is observed across Vera Rubin ridge (VRR) A Mn‐rich interval is observed stratigraphically above the decrease in clay mineral content on VRR VRR likely resulted from increased induration from late‐stage fluid interactions long after the lake environment in Gale crater ceased